ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPUASAN KERJA PADA KARYAWAN DI PT.X - Muhammad Reza Rusman; Ida Wahyuni; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Employee’s job satisfaction is very important to increase the motivation of employee that can affect the productivity of the employee and the company. The impact of job dissatisfaction may be decreasing productivity, increased turnover and absenteeism. The aim of this research was to analyze the relationship between job, supervision, salary, promotion and co-workers with the level of employee satisfaction in PT.X. The method of this research was explanatory research with cross sectional approach. The population in the study were 40 employees in PT.X with total sampling method. The data collection used a questionnaire JDI (Job Descriptive Index). Then statistical analysis used rank spearman correlation test. The results showed that there were relationship between the job itself (sig = 0.030), supervision (sig = 0.0001), salary (sig = 0.005) and promotional opportunities (sig = 0.019) with the level of job satisfaction. In the other hand, only co-workers variable (sig = 0.106), which showed no correlation with the level of job satisfaction. 52,5% employees were satisfied with their jobs. For improving employee’s job satisification, it will better if Companies provide employees variation in job to avoid boredom in work, increasing informal interaction from top to down besides work time, and fixing the salary or intensive system to employees so it could enhance job satisfaction in employees.